Real time fuzzy logic controlled fire detection system for home applications. (8th November 2019) - Deniz, Vacip; Çunkaş, Mehmet
In this study, a low-cost alternative method for hardware implementation in fire detection has been developed for home or office applications by using fuzzy logic. The system consists of smoke, flame, heat and humidity sensors which are used to detect the fire. When a possible fire is detected, the data from the sensors are processed with fuzzy logic and the result is sent as a message to the mobile phone through the GSM module indicating the fire location in minimum time period. In addition, the sensor values can be monitored by the MQTT Dash application on the mobile phone. A fire test cabinet has been designed to test the developed method. Real time tests were done in the fire test cabinet and it was observed that the fire status was accurately detected in a short time. This study, which is important for researchers and practitioners, offers a different approach to fire detection, especially a new framework for home and office applications, and also helps fire-fighters to respond quickly to fire.